Monolayer Two‐dimensional Molecular Crystals for an Ultrasensitive OFET‐based Chemical Sensor. Issue 11 (29th January 2020) - Li, Haiyang; Shi, Yanjun; Han, Guangchao; Liu, Jie; Zhang, Jing; Li, Chunlei; Liu, Jie; Yi, Yuanping; Li, Tao; Gao, Xike; Di, Chongan; Huang, Jia; et al.
Abstract: The sensitivity of conventional thin‐film OFET‐based sensors is limited by the diffusion of analytes through bulk films and remains the central challenge in sensing technology. Now, for the first time, an ultrasensitive (sub‐ppb level) sensor is reported that exploits n‐type monolayer molecular crystals (MMCs) with porous two‐dimensional structures. Thanks to monolayer crystal structure of NDI3HU‐DTYM2 (NDI) and controlled formation of porous structure, a world‐record detection limit of NH3 (0.1 ppb) was achieved. Moreover, the MMC‐OFETs also enabled direct detection of solid analytes of biological amine derivatives, such as dopamine at an extremely low concentration of 500 ppb. The remarkably improved sensing performances of MMC‐OFETs opens up the possibility of engineering OFETs for ultrasensitive (bio)chemical sensing. Abstract : MMCs make sense : Two‐dimensional porous and nonporous monolayer molecular crystals (MMCs) of NDI3HU‐DTYM2 (NDI) were controllably synthesized by drop‐casting on different substrates. Both MMC sensors based on organic field‐effect transistors show high‐sensitivity performance to NH3 vapor. The porous MMC showed relative sensitivity of 72 % upon exposure to 0.1 ppb NH3, while the fluorescent intensity decreased by 40.9 % when exposed to 10 ppb NH3 .